2022
DOI: 10.3390/healthcare10081517
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Infection Control Practices of Nurses at University Hospitals

Abstract: This study was conducted to check the extent of nursing professionalism, time pressure, infection control, organizational culture, and the infection control practices of nurses, and to assess the factors that impart an influence on their infection control practices. This is a descriptive survey study aimed at the assessment of factors that impart an influence on the infection control practice of nurses by using a structuralized questionnaire. As the result of this study, the infection control practices of nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our data suggest that these changes were based on the implementation of a working model of nosocomial infection prevention and control by NICI During the COVID-19 epidemic, masks, gloves, and hand sanitizer were used to prevent transmission because respiratory droplets and contact are the main routes of transmission. Mask wearing compliance is high among Chinese people and people in other countries are realizing the importance of wearing masks (Lee,, et al, 2022). However, there were issues with the use of personal protective equipment, such as masks may be too loosely laced, face screens may not have been implemented in high-risk departments, and gloves were done incorrectly.…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggest that these changes were based on the implementation of a working model of nosocomial infection prevention and control by NICI During the COVID-19 epidemic, masks, gloves, and hand sanitizer were used to prevent transmission because respiratory droplets and contact are the main routes of transmission. Mask wearing compliance is high among Chinese people and people in other countries are realizing the importance of wearing masks (Lee,, et al, 2022). However, there were issues with the use of personal protective equipment, such as masks may be too loosely laced, face screens may not have been implemented in high-risk departments, and gloves were done incorrectly.…”
Section: Resultsmentioning
confidence: 99%
“…Suboptimal IPC, including inadequate decontamination and poor hand hygiene, are the most frequently raised transmission issues ( Islam et al, 2020 ; Shbaklo et al, 2021 ; Wee et al, 2021 ). The spread of infection is also caused by the lack of nurse compliance in IPC so this will have an impact on the performance of nurses ( Lee & Jun, 2022 ). Previous studies reported that the lack of adherence in carrying out IPC such as hand washing, using personal protective equipment, and other practices can be caused by a lack of knowledge about proper techniques, supplies, supervision, and motivation of nurses at work ( Alhumaid et al, 2021 ; Driscoll & Evans, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prevention and control are important areas of study for nurses, particularly in the field of IPC. IPC nurses are qualified to use effective methods to prevent the spread of infections and ensure the safe management of patients with infectious diseases [ 13 ]. They can educate healthcare professionals about the risk of hospital-acquired infections and advise them on how to reduce these risks.…”
Section: Introductionmentioning
confidence: 99%